Acceptability and Future Considerations for Telegenetic Counseling After the COVID Pandemic: Interviews with Genetic Counselors, Clinicians, and Patients - Meghan C. Martinez MPH; Nina Szwerinski MS; Su-Ying Liang PhD; Sharon Chan MPH; Monique de Bruin MD; Cheryl D. Stults PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
While telegenetic counseling has increased substantially since the start of the COVID-19 pandemic, previous studies reported concerns around building rapport, nonverbal communication, and the patient-counselor relationship. This qualitative evaluation elicited feedback from genetic counselors, referring clinicians, and patients from a single healthcare organization to understand the user-driven reasons for overall satisfaction and experience. We conducted 22 in-depth, semi-structured interviews with participants from all 3 groups between February 2022 and February 2023. Interview recordings were transcribed and analyzed using a pragmatic thematic approach. Participants across all groups felt the style and content of the genetic counseling visit lent itself perfectly to telegenetics specifically because of no physical exam component. Most patient and counselor participants expressed having the genetic counseling over phone or video had no impact on the patient-counselor relationship or the amount of trust and emotional connection they were able to achieve remotely. Preference for visit type can be influenced by in-person masking requirements impeding full facial expressions or expressing strong emotions over phone. All respondents expressed strong support for all modalities going forward. Counselors with broad experience across platforms should be the focus of future recruitment as should patient education around the nature of the genetic counseling visit and the accuracy of various testing options. Telegenetic programs should consider perspectives from all 3 groups to ensure that specific needs of each are addressed.